RESEARCH ON STAGED FATIGUE DAMAGE OF ALUMINUM ALLOY 6061-T6 - GENG MeiLing; YANG YaLi; CHEN Hao; WANG YiPeng; LI YongFang (Jixie qiangdu)
It is of great theoretical significance and engineering value to carry out fatigue damage detection and evaluation of aluminum alloy for application of automobile lightweight materials. In this paper,the periodic fatigue damage characteristics of 6061-T6 aluminum alloy were studied based on CT damage detection and defect reconstruction technology. Firstly,fatigue damage samples of 6061-T6 aluminum alloy at different stages are obtained by static tensile test and periodic fatigue test. Secondly,defect information of holes and cracks in the damaged samples are achieved through X-ray CT scanning,and 3D reconstruction of defect features is carried out by AVIZO visualization software,and continuity features of the damage defects in different stages are studied. Finally,the change characteristics of damage evolution parameters,including porosity,damage volume fraction,are analyzed according to damage degree of fatigue damage samples in different stages. Based on the analysis of change of damage characterization parameters with the number of cycles,the damage volume fraction,as a damage parameter,determines the proportion of damage,and has a direct impact on the size of damage,which can better reflect the continuous change of damage,so as to conduct a reasonable and effective analysis of defect evolution process.